Individual differences in song plasticity in response to social stimuli and singing position. Issue 5 (2nd May 2022) - Jablonszky, Mónika; Canal, David; Hegyi, Gergely; Krenhardt, Katalin; Laczi, Miklós; Markó, Gábor; Nagy, Gergely; Rosivall, Balázs; Szász, Eszter; Zsebők, Sándor; Garamszegi, László Zsolt
Abstract: Individual animals can react to the changes in their environment by exhibiting behaviors in an individual‐specific way leading to individual differences in phenotypic plasticity. However, the effect of multiple environmental factors on multiple traits is rarely tested. Such a complex approach is necessary to assess the generality of plasticity and to understand how among‐individual differences in the ability to adapt to changing environments evolve. This study examined whether individuals adjust different song traits to varying environmental conditions in the collared flycatcher ( Ficedula albicollis ), a passerine with complex song. We also aimed to reveal among‐individual differences in behavioral responses by testing whether individual differences in plasticity were repeatable. The presence of general plasticity across traits and/or contexts was also tested. To assess plasticity, we documented (1) short‐scale temporal changes in song traits in different social contexts (after exposition to male stimulus, female stimulus or without stimuli), and (2) changes concerning the height from where the bird sang (singing position), used as a proxy of predation risk and acoustic transmission conditions. We found population‐level relationships between singing position and both song length (SL) and complexity, as well as social context‐dependent temporal changes in SL and maximum frequency (MF). We found among‐individual differences in plasticity of SL and MF along both the temporal and positional gradients. These among‐individual differences in plasticity were repeatable. Some of the plastic responses correlated across different song traits and environmental gradients. Overall, our results show that the plasticity of bird song (1) depends on the social context, (2) exists along different environmental gradients, and (3) there is evidence for trade‐offs between the responses of different traits to different environmental variables. Our results highlight the need to consider individual differences and to investigate multiple traits along multiple environmental axes when studying behavioral plasticity. Abstract : This study examined in the collared flycatcher ( Ficedula albicollis ), whether individuals adjust different song traits to varying environmental conditions. We recorded a population‐level relationship between singing position and song length (SL), and repeatable among‐individual differences in plasticity of SL and maximum frequency along both the temporal (order) and positional (singing position) gradients. Our results show that the plasticity of bird song exists along different environmental gradients and that it may potentially evolve.